Focused Ultrasound for Noninvasive, Focal Pharmacologic Neurointervention - Wang, Jeffrey B.; Di Ianni, Tommaso; Vyas, Daivik B.; Huang, Zhenbo; Park, Sunmee; Hosseini-Nassab, Niloufar; Aryal, Muna; Airan, Raag D. (Frontiers in Neuroscience, 2020)
A longstanding goal of translational neuroscience is the ability to noninvasively deliver therapeutic agents to specific brain regions at the right time. Focused ultrasound (FUS) is an emerging technology that can noninvasively deliver high amounts of energy with millimeter and millisecond resolution to any point in the human brain with FDA-approved hardware. Although FUS is clinically utilized primarily for focal ablation in conditions such as essential tremor, recent breakthroughs have enabled the use of FUS for drug delivery. In this review, we present strategies for image-guided FUS-mediated pharmacologic neurointerventions. First, we discuss blood-brain barrier opening to deliver therapeutic agents of a variety of sizes to the central nervous system. We then describe the use of ultrasound-sensitive nanoparticles to noninvasively deliver small molecules to millimeter-sized structures within the brain without the need for blood-brain barrier opening. We also consider the safety and potential complications of these techniques, with attention to temporal acuity. Finally, we close with a discussion of different methods for mapping the ultrasound field within the brain and describe future avenues of research in ultrasound-targeted drug therapies.